ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU MINCE FISH NILAPADA PRODUK UMKM CV SAKANA INDO PRIMA - Is roni (Jurnal Akrab Juara, 2019)
This study aims to analyze the inventory of CV Sakana Indo Prima Micro Small and Medium Enterprises (UMKM). In this study, the discussion focused on the supply of raw materials for mince tilapia fish. The problem discussed in the research is how to determine the optimal inventory in the company so that the total inventory costs incurred by the company are more efficient. To describe and analyze research data the method used is EOQ (Economic Order Quantity). The object of research is the amount of inventory, the number of purchases, the amount of usage of raw materials used in production, ordering costs and storage costs of raw materials. The data used is the period of 2014-2018. The data collection method used in the research is documentation study. Based on the results of the study, it is known that company policy in determining inventory is still not appropriate. This can be seen from the results of research that the number of purchases and costs for inventory based on company policy so far is higher than the calculation using the EOQ method. The difference in inventory costs shows that with the EOQ method in 2014 the company can save the total cost of raw material for mince tilapia by Rp. 816,667, in 2015 amounting to Rp. 881,490, in 2016 amounting to Rp. 6,243,484, 2017 amounting to Rp. 10,997,907, and in 2018 Rp. 8,285,162